2022
DOI: 10.1063/5.0073527
|View full text |Cite
|
Sign up to set email alerts
|

Uniform supersonic flow sampling for detection by chirped-pulse rotational spectroscopy

Abstract: Chirped-pulse Fourier transform microwave (CP-FTMW) spectroscopy is a powerful near-universal detection method finding application in many areas. We have previously coupled it with supersonic flows (CPUF) to obtain product branching in reaction and photodissociation. Because chirped-pulse microwave detection requires monitoring the free induction decay on the timescale of microseconds, it cannot be employed with good sensitivity at the high densities achieved in some uniform supersonic flows. For application t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Using the C 3 H 3 + NH 2 /ND 2 reaction, we show that chemical dynamics of a wide variety of reactions can be investigated using the CPUF-mmW approach. Applications of CPUF-mmW extend beyond the investigation of reaction dynamics; future generations of CPUF-mmW experiments will enable precise measurements of absolute rate coefficients of complex reactions by exploiting its ability to detect and quantify reactants and products simultaneously at well-defined conditions …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using the C 3 H 3 + NH 2 /ND 2 reaction, we show that chemical dynamics of a wide variety of reactions can be investigated using the CPUF-mmW approach. Applications of CPUF-mmW extend beyond the investigation of reaction dynamics; future generations of CPUF-mmW experiments will enable precise measurements of absolute rate coefficients of complex reactions by exploiting its ability to detect and quantify reactants and products simultaneously at well-defined conditions …”
mentioning
confidence: 99%
“…Applications of CPUF-mmW extend beyond the investigation of reaction dynamics; future generations of CPUF-mmW experiments will enable precise measurements of absolute rate coefficients of complex reactions by exploiting its ability to detect and quantify reactants and products simultaneously at well-defined conditions. 48 ■ ASSOCIATED CONTENT * sı Supporting Information…”
mentioning
confidence: 99%
“…The CPUF experimental setup consisting of a pulsed Laval flow coupled to a chirped pulse millimeter-wave spectrometer is discussed in our previous publications. ,, Therefore, only a brief experimental description relevant to this study is provided below. In this work, propargyl bromide (99%, Sigma-Aldrich) and 1,2-butadiene (98% Chemsampco) were used as precursor molecules for the propargyl radical.…”
Section: Methodsmentioning
confidence: 99%
“…We apply chirped pulse rotational spectroscopy in a pulsed flow (CPUF) to investigate the gas phase bimolecular reaction dynamics of NO + C 3 H 3 . In previous studies, we demonstrated the successful application of CPUF for product branching determinations in unimolecular and bimolecular reactions with isomer and vibrational level specificity, and we have recently shown application to low-temperature kinetics determination employing sampling. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation